Renvoi Prosedur sebagai Upaya Hukum Terhadap Tagihan Kreditur yang Ditolak oleh Kurator dalam Perkara Kepailitan (Studi Putusan Renvoi Prosedur Nomor 28/Pdt.Sus Pkpu/2018/Pn.Niaga.Jkt.Pst ) - Satriadi, Dharma; Rifai, Anis (UNES Law Review, 2023)
The Renvoi procedure is a legal mechanism that aims to protect the rights of creditors who face a refusal of payment by the receivership in the context of insolvency. This process provides a legal recourse for creditors who face rejection of bills by sending a letter of objection supporting the reasons for the rejection, complete with relevant evidence, to the Panel of Deciding Judges through the role of the Supervisory Judge. In this Renvoi Procedure case, PT JIEP as the Applicant and the Curator Team of PT Tobu Indonesia Steel as the Respondent made legal efforts because the Applicant submitted an objection to the bill to the Respondent. In this study, the author chose to apply a normative descriptive approach. The technique chosen involves a statute-based approach as well as a case-based approach to analyze and explore the issues discussed where this approach is used to examine cases that occur based on statutory provisions relating to all bankruptcy activities in PKPU. Based on the summary that has been submitted, the author develops a more in-depth research on Decision Number 28/Pdt.Sus-PKPU/2018/PN.Niaga.Jkt.Pst.